Peran KPK dalam Memberantas Korupsi di Indonesia : Studi Kasus Dugaan Korupsi Program Makan Siang Gratis - Veronika Christine Mevelia; Devina Shava Amalia; Tries Ellia Sandari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Corruption is a structural problem that continues to hamper development and equitable welfare in Indonesia. The data sources used consist of 13 national scientific journals, 3 reports from non-governmental organizations (ICW, KPK, TII), and 4 credible mass media outlets (Kompas, Tempo, CNBC Indonesia, and BBC Indonesia) published between 2019 and 2025. The purpose of this article is to evaluate the consistency and institutional challenges in anti-corruption efforts, as well as to recommend strengthening the integrity system in public policy governance in the future. Based on an analysis of three strategic cases—e-KTP, COVID-19 social assistance, and the free lunch program—the role of the Corruption Eradication Commission (KPK) shows a transformation from a repressive approach to a more preventive and systemic one. In the e-KTP and social assistance cases, the KPK emphasized its strong law enforcement function, while in the free lunch program, the KPK positioned itself as a strategic supervisor from the planning stage to prevent potential irregularities.